Adalékok Kelet-Közép-Európa térszerkezetének felrajzolásához - Rechnitzer, János (Közép-Európai Közlemények, 2013)
The past few years have seen a dramatic increase in the number of Hungarian and international investigations and studies on East-Central Europe. From a geopolitical aspect this increase is warranted. This region is located between West and East. In an environment of fluctuating political emphases this position has been and will continue to be validated in unique ways. Analyses view the “Central European Boomerang” connecting the cities Gdansk–Poznan–Wroclaw–Prague–Brno–Bratislava–Budapest as East-Central Europe’s western developmental zone. The countries of the region display a development pattern in which the levels of eastern ad western regions are markedly different. A general tendency is for regional resources to be concentrated in capital cities and their wider agglomerations, which are consistently prominent. Beyond capital cities only a few large urban areas or regional centers are able to demonstrate a fast development dynamic. This article analyses the processes of spatial structure of the East-Central European region in detail, outlining current and anticipated spatial development directions.